Analysis of Efforts to Overcome Voltage Drops by Installing Substations in Low Voltage Networks with ETAP Simulation - IG Suputra Widharma; IN Sunaya; IGN Sangka; IM Sajayasa; IKG Sri Budarsa (Frontier Energy System and Power Engineering, 2023)
Electric power is an energy of secondary that generated, transmitted and distributed to consumers and used to many activities. Electrical power system is electrical power installation system is consists of generation system, transmitting system, and distribution system that integration and function to supply electric power consumption. For this purpose, both of quantity and quality also continuity in PT PLN wished can be provides and distributes electric power to consumers and all of people. One of the main materials of the distribution network to distribute electric power to customers is the distribution substation in which there is a transformer. Transformer as a means of distribution of electrical energy is susceptible to interference. Distribution substation SM 0075 Feeder Bajera is one of the distribution substations that experienced a voltage drop at the end of the JTR in the C direction. So, to fix the problems that occurred, PT. PLN has added a substation. With the addition of substations, it is necessary to pay attention to the power losses that arise, not to cause greater power losses. Based on the results of the calculations at the distribution substation SM0075 Bajera feeder before and after the addition of the insertion substation, it was found that the voltage drop at the end of the JTR direction C at the SM0075 distribution substation was 22.638% in the R phase, 15.745% in the S phase and 14.005% in the T phase. the result of the addition of the substation is a smaller power loss with the difference before and after that is equal to 2739.986472 Watt. then viewed from the quality of the voltage and environmental conditions, the C18D6A1D3 pole is better for insertion substations than the C18D6A1D2 pole based on the Etap 12.6 simulation.